AI is helping companies redefine, not just improve, performance - Schrage, Michael; Kiron, David; Candelon, François; Khodabandeh, Shervin; Chu, Michael (MIT Sloan Management Review, 2023)
In this first article in a series of four, the researchers behind the 2023 MIT Sloan Management Review-BCG Artificial Intelligence and Business Strategy Big Ideas research project outline the opportunities AI brings for key performance indicators and strategic measurement. They discuss the business implications of using AI to generate and refine KPIs and explain how enabling strategic measurement systems to learn fundamentally alters how organizations understand and invest in future performance.
Reprint 64435. - Includes bibliographical references
Keywords: Artificial intelligence; Business planning; Intelligence artificielle; artificial intelligence